Pelatihan Pemanfaatan Software Pendukung Statistik Dalam Pengolahan Data Kuantitatif Bagi Guru-Guru SMA - Herlawati, Herlawati; Atika, Prima Dina; Handayanto, Rahmadya Trias; Sumadyo, Malikus; Samsiana, Seta; Gunarti, Anita Setyowati Srie; Maimunah, Maimunah (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Teachers need additional knowledge of quantitative data processing using statistical support software because of the diverse educational backgrounds of teachers such as education science, management science, although there are also those whose educational background is mathematics and natural sciences (MIPA). In addition, the level of awareness of teachers to study statistics for processing quantitative data is still low and is considered less important. Solutions that can be given to this community service activity include organizing training on the use of statistical support software to provide understanding and skills in the use of such software, including Microsoft Ms.Excel and Matlab Mobile in an effective and efficient manner. This can be done through the mentoring process in this activity and will be followed by other advanced trainings. The results of this training, based on a survey using an online mentimeter, showed that it was very useful and the participants wanted to continue this training with the theme of using the Statistical Package for the Social Sciences (SPSS).